Structural, magnetic, elastic, and dielectric properties of Mn0.3−xCdxCu0.2Zn0.5Fe2O4 nanoparticles - Beyranvand, Morteza; Gholizadeh, Ahmad (Journal of materials science. Materials in electronics, 2020)
The doping of the spinel ferrites with selective dopants usually improves the properties of the parent ferrite. In this paper, the structural, magnetic, elastic, and dielectric properties of Mn 0.3− x Cd x Cu 0.2 Zn 0.5 Fe 2 O 4 ( x = 0.00–0.30, in steps of 0.05) via citrate–nitrate method were reported. The samples were structurally characterized using the techniques of X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), field-emission scanning electron microscopy, and energy-dispersive X-ray spectroscopy. The Rietveld refinement of XRD patterns showed the formation of the spinel phase of the samples that can be indexed in the cubic symmetry with the Fd-3m space group confirmed by FTIR spectrometry. The nonmonotonic variant of saturation magnetization with an increase of Cd substitution can be explained based on the different cation distribution in the tetrahedral and octahedral sites of spinel structure and Yaffet–Kittel-type noncollinear ordering. According to the dielectric results, the conduction arises for x = 0.05, 0.10, 0.15, 0.25, and 0.30 is due to the short-range translation hopping assisted by small polaron mechanism and for x = 0.00 and 0.20 is ascribed to the localized orientation hopping assisted by large polaron.